La representación femenina en la serie de televisión juego de tronos: estudio de percepciones de fans peruanos - Padilla Silva, Karla Sofia (2021)
The main objective of this research work was to know the perceptions that Peruvian fans of the television series Game of Thrones have regarding the female characters. Currently, the representations of gender that are made on television have a certain impact on society because this medium can generate various debates and influences regarding the roles established for both women and men. It is considered that this study is relevant to continue knowing how people interpret the representation of women in television series. In that sense, qualitative methodology was used in order to know in greater depth the opinions and thoughts of the fans regarding this topic. In this study, 20 in-depth interviews were conducted with both men and women using a guide that contained 16 questions in total. The results showed that the participants considered the female characters strong, resilient and intelligent, as well as capable of breaking patterns in the fictional society of Game of Thrones, also visualizing the difficulties that occurred in this representation to reach a situation of empowerment. With this, it is concluded that the perceptions of the interviewees regarding the women in the series were positive, at the same time that they understood the complexity of being a woman in a world with strict rules and schemes in a fictional sexist society as shown in the series.